PELUANG BISNIS SHOPEE AFFILIATE: MENGUBAH HOBI BELANJA ONLINE JADI CUAN - Domara, Novita Ayu; Akbar, Maulana; Adhim, Mohammad Fatahillah Fauzil (UIN Sunan Kalijaga, 2025)
Shopee Affiliate is an affiliate program that offers opportunities for young people to generate income through product promotion on the Shopee e-commerce platform. This article aims to analyze the potential of Shopee Affiliate as an easily accessible and relevant digital business solution for the younger generation. The method used in this article is an observation and evaluation of the Shopee Affiliate socialization and training seminar held for the target group of youth in the local community. The discussion covers the basic concept of Shopee Affiliate, registration steps, effective promotion strategies, and the benefits of this program for participants. Based on the training results, it was found that Shopee Affiliate is able to provide business opportunities without large capital with high time flexibility. The conclusion of this article confirms the importance of practice-based training to help young people understand and optimize the Shopee Affiliate program as a sustainable digital economy opportunity.